Therapeutic efficacy of ozonated blood in severe COVID-19 patients: a randomized controlled trial - Salmanzadeh, Shokrollah; Sheibani, Behnam; Bitaraf, Saeid; Nashibi, Roohangize; Moogahi, Sasan (Frontiers in Medicine, 2025)
IntroductionDuring the COVID-19 pandemic, several studies were published on the use of ozone therapy in treating COVID-19, leveraging pre-pandemic published data on the anti-inflammatory, antimicrobial, and immunomodulatory properties of ozone gas. In this pilot randomized controlled trial conducted during the pandemic, we aimed to assess the outcomes of blood ozone therapy (OT) as an investigational agent versus the COVID-19 standard of care as standalone on 60 patients diagnosed with severe COVID-19.MethodsThis study was conducted as a randomized controlled trial in which both arms of the study received the Iranian Health Ministry’s COVID-19 treatment guideline as the standard of care; the intervention group additionally received intravenous ozonated blood based on the related international society guidelines.ResultsOur findings revealed a statistically non-significant 33% higher hazard ratio for a prolonged hospital stay in the OT group. However, the OT arm exhibited a significantly higher odds ratio of 4.3 for ICU transfer of patients initially admitted to general wards. The univariate logistic regression analysis of mortality found a 3.5-fold increased probability associated with OT use, though this difference was not statistically significant.ConclusionWe suggest that further trials with robust study designs utilizing larger populations are required to further assess the role of OT on severe COVID-19 keeping in mind a heightened awareness of potential unfavorable outcomes throughout the study.Clinical trial registrationhttps://irct.ir, identifier IRCT20200616047792N1.